2021
DOI: 10.1167/iovs.62.9.16
|View full text |Cite
|
Sign up to set email alerts
|

Myopia in African Americans Is Significantly Linked to Chromosome 7p15.2-14.2

Abstract: The purpose of this study was to perform genetic linkage analysis and association analysis on exome genotyping from highly aggregated African American families with nonpathogenic myopia. African Americans are a particularly understudied population with respect to myopia. METHODS.One hundred six African American families from the Philadelphia area with a family history of myopia were genotyped using an Illumina ExomePlus array and merged with previous microsatellite data. Myopia was initially measured in mean s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…Recently, Simpson, C. L. and colleagues identified a significant chain peak of myopia in African American families at 7p15.2 and 7p14.2 [ 30 ]; meanwhile, Musolf AM et al [ 31 ] also reported a significant genetic linkage peak of myopia in Chinese Han patients at 10q26. 13.…”
Section: Heredity and Myopiamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Simpson, C. L. and colleagues identified a significant chain peak of myopia in African American families at 7p15.2 and 7p14.2 [ 30 ]; meanwhile, Musolf AM et al [ 31 ] also reported a significant genetic linkage peak of myopia in Chinese Han patients at 10q26. 13.…”
Section: Heredity and Myopiamentioning
confidence: 99%
“… 2017 [ 26 ] TNFRSF21 Pan, H. 2019 [ 27 ] AGRN Zheng, Y. H. 2021 [ 28 ] P4HA2 Napolitano, F. 2018 [ 29 ] 7p15.2 and 7p14.2 Simpson, C.L. 2021 [ 30 ] 10q26. 13.…”
Section: Heredity and Myopiamentioning
confidence: 99%
“…The Transmission Disequilibrium Test (TDT) stands out as a powerful tool for pinpointing disease-associated loci that exhibit strong genetic in uence in complex disorders, often mirroring the behavior of Mendelian alleles in monogenic conditions within trio family cohorts [20,21]. Diverging from traditional case-focused sequencing strategies that prioritize exons and splice junctions to uncover mutations adhering to classic Mendelian patterns, TDT facilitates the unbiased discovery of disease-related loci throughout the genome, without heavy reliance on presupposed models of inheritance [22][23][24]. Consequently, TDT can enhance existing sequencing methodologies by uncovering signi cant genetic factors that may otherwise remain undetected…”
Section: Introductionmentioning
confidence: 99%
“…Any comparison of the African American participants in this analysis with other minority or even nonminority groups needs to be considered within the context of both the genetic and the SDOH environment at the time the study was performed. Although African American individuals with myopia have been found to have a specific chromosomal linkage, 5 it remains unclear if this genetic association makes refractive errors more or less common than the refractive errors found in other racial and ethnic populations. 6,7 Similarly, although Dhablania et al 1 were able to capture many aspects of SDOH, it is very difficult to compare their results with other studies performed many years earlier when the SDOH environment was likely to be very different and not as thoroughly assessed.…”
mentioning
confidence: 99%